Influence of Office Automation on Secretarial Administrators’ Effectiveness in Ogun State-Owned Universities - Dosunmu, Margaret Moronke; Bukki, Abolaji O.; Akintola, Olugbenga A. (NIU Journal of Social Sciences, 2018)
The effectiveness of a secretary in an organization strongly depends on the available office technology as well as the skills and competencies of such secretary to perform office duties. Office automation is designed to redefining the office work; improve the appearance and accuracy of output that completely changed the old way of performing office tasks and being replaced with a new business orientation thereby making the old method to be outdated. This research work examined the influence of office automation on secretariesâ€™ effectiveness in the state-owned universities in Ogun State.  Four (4) research questions were answered in line with the objective of the study.  A structured questionnaire was designed and validated. Data collected were analyzed using regression analysis at 0.05 level of significance.  The result of the findings indicated that there was no significant influence of office automation on secretariesâ€™ interpersonal skills, personal quality, professional behavior and job related skills. It was recommended among others that Secretaries should attend seminars, conferences and workshops to develop them in the area of information technologies and Microsoft office packages. Also, it was recommended that the University Management should continually organize in-service training for the Secretaries to teach them newly automated machines. Keywords: Office, automation, Secretarial Administrators and Universities